Value versus growth investing: Why do different investors have different styles? - Cronqvist, Henrik; Siegel, Stephan; Yu, Frank (Journal of Financial Economics, 2015)
We find that several factors explain an individual investor׳s style, i.e., the value versus growth orientation of the investor׳s stock portfolio. First, we find that an investor׳s style has a biological basis and is partially ingrained in an investor from birth. Second, we show that an investor׳s hedging demands as well as behavioral biases explain investment style. Finally, an investor׳s style is explained by life course theory in that experiences, both earlier and later in life, are related to investment style. Investors with adverse macroeconomic experiences (e.g., growing up during the Great Depression or entering the labor market during an economic recession) or who grow up in a lower socioeconomic status rearing environment have a stronger value orientation several decades later. Our research contributes a new perspective to the long-standing value and growth debate in finance.